Loss‐of‐function variants in NFIA provide further support that NFIA is a critical gene in 1p32‐p31 deletion syndrome: A four patient series. Issue 12 (22nd September 2017) - Revah‐Politi, Anya; Ganapathi, Mythily; Bier, Louise; Cho, Megan T.; Goldstein, David B.; Hemati, Parisa; Iglesias, Alejandro; Juusola, Jane; Pappas, John; Petrovski, Slavé; Wilson, Ashley L.; Aggarwal, Vimla S.; et al.
Abstract : The association between 1p32‐p31 contiguous gene deletions and a distinct phenotype that includes anomalies of the corpus callosum, ventriculomegaly, developmental delay, seizures, and dysmorphic features has been long recognized and described. Recently, the observation of overlapping phenotypes in patients with chromosome translocations that disrupt NFIA (Nuclear factor I/A), a gene within this deleted region, and NFIA intragenic deletions has led to the hypothesis that NFIA is a critical gene within this region. The wide application and increasing accessibility of whole exome sequencing (WES) has helped identify new cases to support this hypothesis. Here, we describe four patients with loss‐of‐function variants in the NFIA gene identified through WES. The clinical presentation of these patients significantly overlaps with the phenotype described in previously reported cases of 1p32‐p31 deletion syndrome, NFIA gene disruptions and intragenic NFIA deletions. Our cohort includes a mother and daughter as well as an unrelated individual who share the same nonsense variant (c.205C>T, p.Arg69Ter; NM_001145512.1). We also report a patient with a frameshift NFIA variant (c.159_160dupCC, p.Gln54ProfsTer49). We have compared published cases of 1p32‐p31 microdeletion syndrome, translocations resulting in NFIA gene disruption, intragenic deletions, and loss‐of‐function mutations (including our four patients) to reveal that abnormalities of the corpus callosum, ventriculomegaly/hydrocephalus, macrocephaly, Chiari I malformation, dysmorphic features, developmental delay, hypotonia, and urinary tract defects are common findings. The consistent overlap in clinical presentation provides further evidence of the critical role of NFIA haploinsufficiency in the development of the 1p32‐p31 microdeletion syndrome phenotype.